Engineering a material for biomedical applications with electric field assisted processing - Ahmad, Z; Nangrejo, M; Edirisinghe, M; Stride, E; Colombo, P; Zhang, H (2009)
In this work, using multiple co-flows we demonstrate in-situ encapsulation of nano-particles, liquids and/or gases in different structural morphologies, which can also be deposited in a designated pattern by a direct write method and surface modification can be controlled to release encapsulated material. The range of possibilities offered by exposing a material solution to an applied electric field can result in a plethora of structures which can accommodate a whole host of biomedical applications from microfluidic devices (microchannels, loaded with various materials), printed 3D structures and patterns, lab-on-a-chip devices to encapsulated materials (capsules, tubes, fibres, dense multi-layered fibrous networks) for drug delivery and tissue engineering. The structures obtained in this way can vary in size from micrometer to the nanometer range and the processing is viable for all states of matter. The work shown demonstrates some novel structures and methodologies for processing a biomaterial. © 2009 Springer-Verlag.